Seasonal change and microhabitat association of Arctic spider assemblages (Arachnida: Araneae) on Victoria Island (Nunavut, Canada). Issue 3 (20th March 2017) - Cameron, Elyssa R.; Buddle, Christopher M.
Abstract: Arctic ecosystems are characterised by a mosaic of distinct microhabitats, which play a key role in structuring biodiversity. Understanding species diversity in relation to these microhabitats, and how communities are structured seasonally, is imperative to properly conserve, monitor, and manage northern biodiversity. Spiders (Arachnida: Araneae) are dominant arthropod predators in the Arctic, yet the seasonal change in their communities in relation to microhabitat variation is relatively unknown. This research quantified how spider assemblages are structured seasonally and by microhabitat, near Cambridge Bay, Nunavut, Canada. In 2014, spiders were collected in 240 pan and pitfall traps placed in common microhabitat types (two wet and two dry) from 3 July to 11 August, the active season in the high Arctic. In total, 10 353 spiders from 22 species and four families were collected. Non-metric multidimensional scaling ordinations revealed that spider assemblages from wet habitats were distinct from those occurring in drier habitats, but that differences within each of those habitats were not evident. Abundance and diversity was highest in wet habitats and differed significantly from dry habitats; both these variables decreased seasonally. Spider assemblages in the north are structured strongly along moisture gradients, and such data informs planning for future ecological monitoring in the Arctic.